Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
a = -25
b = [tex]\frac{33}{2}[/tex]
Step-by-step explanation:
Step 1 - Subtract 36 from both sides of the first equation:
a + 36 = 11
a + 36 - 26 = 11 - 36
a = -25
Step 2 - Substitute in the known a value:
a + 2b = 8
-25 + 2b = 8
Step 3 - Add 25 to both sides:
-25 + 2b + 26 = 8 + 25
2b = 33
Step 4 - Divide both sides by 2:
2b ÷ 2 = [tex]\frac{33}{2}[/tex]
b = [tex]\frac{33}{2}[/tex]
Hope this helps!
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.